(untitled) (Journal of EAHIL, 2022)
Researchers performing systematic reviews often express the desire to limit the search results to a certain study size. The aim of our study was to develop a filter in embase.com and Ovid to retrieve references above a specified threshold of study size. The filter that was developed consists mainly of truncated numbers in proximity with words such as patients, cases, adults, females and phrases like "n=". Preliminary results showed that the sensitivity of the filter, as evaluated on existing systematic reviews, was at least 94%. The burden of screening for systematic reviews can be greatly reduced with the study size filter.